A comprehensive adsorption study of 1-Hydroxy-2-Naphthoic acid using cost effective engineered materials - Zeb, Muhammad Aurang; Murtaza, Ghulam; Hussain, Muhammad Aamer; Kubra, Khadija Tul; Muvhiiwa, Ralph F.; De Kock, Lueta-Ann; Hassard, Francis (Elsevier, 2020)
The naphthoic acids are challenging and costly to remove from water and soil. 1-Hydroxy-2-Naphthoic acid (HNA) is a phenanthrene decomposition product from petroleum-contaminated environments during the aerobic decomposition of polyaromatic hydrocarbons. The hydrogeological mobility of hydrocarbon breakdown products represent a pollution risk (e.g. for drinking water sources). Adsorption to biochar produced from agricultural by-products is a useful strategy to remediate contaminated wastewaters. Here, we examine the controls on the HNA adsorption to the adsorbents magnetite, clay minerals, biochar and magnetite enriched companion materials, namely the influence of contact time, contaminant concentration and ionization effects at different pH. The adsorption of HNA was investigated using low-cost and readily available adsorbents: (i) wheat straw biochar, (ii) rice husk biochar, (iii) sugarcane biochar, (iv) zeolite, (v) montmorillonite, (vi) magnetite and their enriched magnetic companions. Magnetite enriched biochar exhibited greater adsorption rates compared with their nonmagnetic analogs for HNA. The maximum adsorption capacity of the magnetite enriched compounds (initial water concentration of 0.32 mmol HNA.L) was 0.45 mmol.HNA.g of enriched zeolite. The magnetite enriched biochar and conventional biochar showed similar adsorption kinetics although magnetite enrichment improved the efficacy of adsorption. The adsorption fitted the pseudo-second order model in all cases, suggesting the dominant mechanism of adsorption was chemisorption. The magnetite enrichment reduced intra-particle diffusion, possibly due to fouling or blocking of pores within the particles, as evidenced by the decrease in diffusion rate constants. Overall, HNA adsorption improved after magnetic enrichment due to magnetite competing with inhibition sites on the biochar carriers. These findings translate into equivalence between magnetite and magnetic biochars, suggesting cheaper alternative materials could be synthesized in situ with the biochar acting as both an adsorbent and carrier, increasing the prospect of designer biochars for targeted pollutant removal. This approach has the potential to be used for wastewater treatment or for application as a soil additive for remediation of runoff from contaminated soils.
Keywords: Enriched adsorbents; Zeolite; Organic pollutants; Biochar; 1-Hydroxy-2-Naphthoic Acid; Poly aromatic hydrocarbons